A nitrogen-doped PtSn nanocatalyst supported on hollow silica spheres for acetic acid hydrogenation. Issue 64 (31st May 2018) - Zhou, Jiahua; Zhao, Yujun; Zhang, Jian; Wang, Yue; Gutiérrez, Oliver Y.; Wang, Shengnian; Li, Zhengxiang; Jin, Peng; Wang, Shengping; Ma, Xinbin; Lercher, Johannes A.
Abstract : The interaction between N and Pt significantly enhanced Pt dispersion and the activity in the hydrogenation of acetic acid. Abstract : A novel PtSn/NHSS bimetallic catalyst with N-doped hollow silica spheres as the support was synthesized for the gas-phase hydrogenation of acetic acid to ethanol. Its specific activity was 30% higher than that of PtSn/SiO2 due to the enhanced surface exposure of Pt active sites, induced by the strong interaction between Pt and N.